Adequate vegetative cover decreases nitrous oxide emissions from cattle urine deposited in grazed pastures under rainy season conditions - Chirinda, Ngonidzashe; Loaiza, Sandra; Arenas Calle, Laura N.; Ruíz, Verónica; Faverín, Claudia; Álvarez, Carolina; Savian, Jean Víctor; Belfon, Renaldo; Zuniga, Karen; Morales Rincon, Luis Alberto; Trujillo, Catalina; Arango, Miguel; et al. (Springer, 2019)
A decline in pasture productivity is often associated with a reduction in vegetative cover. We hypothesize that nitrogen (N) in urine deposited by grazing cattle on degraded pastures, with low vegetative cover, is highly susceptible to losses. Here, we quantified the magnitude of urine-based nitrous oxide (N2O) lost from soil under paired degraded (low vegetative cover) and non-degraded (adequate vegetative cover) pastures across five countries of the Latin America and the Caribbean (LAC) region and estimated urine-N emission factors. Soil N2O emissions from simulated cattle urine patches were quantified with closed static chambers and gas chromatography. At the regional level, rainy season cumulative N2O emissions (3.31 versus 1.91 kg N2O-N ha−1) and emission factors (0.42 versus 0.18%) were higher for low vegetative cover compared to adequate vegetative cover pastures. Findings indicate that under rainy season conditions, adequate vegetative cover through proper pasture management could help reduce urine-induced N2O emissions from grazed pastures.